The ten-year survival of the Birmingham hip resurfacing: an independent series. - Murray, D; Grammatopoulos, G; Pandit, H; Gundle, R; Gill, H; McLardy-Smith, P (2012)
Recent events have highlighted the importance of implant design for survival and wear-related complications following metal-on-metal hip resurfacing arthroplasty. The mid-term survival of the most widely used implant, the Birmingham Hip Resurfacing (BHR), has been described by its designers. The aim of this study was to report the ten-year survival and patient-reported functional outcome of the BHR from an independent centre. In this cohort of 554 patients (646 BHRs) with a mean age of 51.9 years (16.5 to 81.5) followed for a mean of eight years (1 to 12), the survival and patient-reported functional outcome depended on gender and the size of the implant. In female hips (n = 267) the ten-year survival was 74% (95% confidence interval (CI) 83 to 91), the ten-year revision rate for pseudotumour was 7%, the mean Oxford hip score (OHS) was 43 (SD 8) and the mean UCLA activity score was 6.4 (SD 2). In male hips (n = 379) the ten-year survival was 95% (95% CI 92.0 to 97.4), the ten-year revision rate for pseudotumour was 1.7%, the mean OHS was 45 (SD 6) and the mean UCLA score was 7.6 (SD 2). In the most demanding subgroup, comprising male patients aged < 50 years treated for primary osteoarthritis, the survival was 99% (95% CI 97 to 100). This study supports the ongoing use of resurfacing in young active men, who are a subgroup of patients who tend to have problems with conventional THR. In contrast, the results in women have been poor and we do not recommend metal-on-metal resurfacing in women. Continuous follow-up is recommended because of the increasing incidence of pseudotumour with the passage of time.